FROM THE QUANTITATIVE TO THE BEHAVIOR: INDEX BOONE APPLICATION IN STRATIGRAPHIC DEPOSITS CHAVIN DE HUANTAR ANALYSIS - Mesía Montenegro, Christian (2014)
In this paper, the Boone Index is applied in the study of 200 strata, distributed among five spatial units, containing more than 20000 archaeological materials that belonged to the Middle and Late Formative periods in Chavin de Huantar’s Wacheqsa Sector. The sample´s size effect was controlled by using Monte Carlo routines, while the Index application allowed the identification of quantitative variations in the archaeological record´s distribution, which in turn reflect distinctions in the activities that took place in the aforementioned spatial units.